Character Education Values in Retno Tanjung Dance Performance As An Identity Dance of The City of Tegal - Giranti, Aulia Haq; Hartono, Hartono; Lestari, Wahyu (Catharsis, 2019)
Retno Tanjung dance is a girl dance coming from the coastal areas of Central Java. It tells about the coastal area women's excitement and gratitude for the abundance of God's gift in the form of seafood. It is also a reflection of Tegal people's thoughts on how the sense of togetherness and the grateful feeling for God's gifts are important. Retno Tanjung dance as the identity dance of Tegal contains a message, meaning and value, one of which is the character education values that are hoped to be able to be conveyed to the society, understood, comprehended, and applied in the people's daily life. In order to analyze this character education values included in Retno Tanjung dance and to analyze the process of the dance to become the identity of the city of Tegal, this research was conducted. In accomplishing the research, the method applied was the qualitative interpretive method which uses interdisciplinary approach. Then, the techniques used to collect the data for the research used were observation, interview, and document study. To validate the data, the triangulation technique of data sources was also applied. Meanwhile, the process of making the dance as the identity dance of Tegal was studied by applying Alo Liliweri's cultural identity theory. The concept of dance basic elements by Jazuli and the concepts of character education values formulated by National Education Ministry were used to analyze the character education values in Retno Tanjung dance. The research result shows that there are some values of character education in the dance. Religious values can be seen in sembahan and Balangan Mega movements, the lyrics of the dance accompaniment, and the use of hijab as the dance costume. Another value is the care for enviroment value which can be seen in the tracat miring, miyak toya, nyerok mina, and piletan mina movements. Retno Tanjung dance as the identity dance of Tegal city can be seen from the behavioral patterns and language used. Kata kunci : Tari Identitas, Nilai Karakter, Retno Tanjung